A hydrophilic magnetic MOF for the consecutive enrichment of exosomes and exosomal phosphopeptides. Issue 90 (23rd October 2020) - Zhang, Ning; Sun, Nianrong; Deng, Chunhui
Abstract : Fe3 O4 @PDA@UIO-66-NH2 is a biocompatible material that can be applied to enrich exosomes and phosphopeptides from urinary exosomes consecutively. Abstract : Hydrophilic Fe3 O4 @PDA@UIO-66-NH2 is employed to consecutively enrich urinary exosomes and exosomal phosphopeptides through the strong bond between Zr and phosphate groups. The recovery of exosomes reached 95% and 707 phosphopeptides were identified from 255 phosphoproteins via LC-MS/MS. This work will make a great contribution to further functional analysis of exosomes.